Should I stay or should I go? A note on employment protection, domestic anchorage, and FDI - Gerda Dewit; Holger Görg; Catia Montagna (Institute for the Study of Labor (IZA), 2003)
This paper examines how employment protection legislation affects location decisions of multinationals. Based on a simple theoretical framework, we estimate an empirical model, using OECD-data on bilateral FDI-flows and employment protection indices. We find that, while an ?unfavourable? employment protection differential between a domestic and a foreign location is inimical to foreign direct investment (FDI), a high domestic level of employment protection tends to discourage outward FDI. The results are in line with our conjecture that strict employment protection in the firm?s home country makes firms reluctant to relocate abroad and keeps them ?anchored? at home.
Keywords: D80; J80; F23; 330; uncertainty; employment protection; foreign direct investment; domestic anchorage; Arbeitsrecht; Kündigungsschutz; Standortfaktor; Direktinvestition; Auslandsproduktion; Schätzung; Theorie; OECD-Staaten